Shift of EMT gradient in 3D spheroid MSCs for activation of mesenchymal niche function - Jeon, Sohee; Lee, Ho-Sun; Lee, Ga-Young; Park, Gyeongsin; Kim, Tae-Min; Shin, Jihye; Lee, Cheolju; Oh, Il-Hoan (NATURE PUBLISHING GROUP, 2017)
Despite the wide use of mesenchymal stromal cells (MSCs) for paracrine support in clinical trials, their variable and heterogeneous supporting activity pose major challenges. While three-dimensional (3D) MSC cultures are emerging as alternative approaches, key changes in cellular characteristics during 3D-spheroid formation remain unclear. Here, we show that MSCs in 3D spheroids undergo further progression towards the epithelial-mesenchymal transition (EMT), driven by upregulation of EMT-promoting microRNAs and suppression of EMT-inhibitory miRNAs. The shift of EMT in MSCs is associated with widespread histone modifications mimicking the epigenetic reprogramming towards enhanced chromatin dynamics and stem cell-like properties, but without changes in their surface phenotype. Notably, these molecular shifts towards EMT in 3D MSCs caused enhanced stem cell niche activity, resulting in higher stimulation of hematopoietic progenitor self-renewal and cancer stem cell metastasis. Moreover, miRNA-mediated induction of EMT in 2D MSCs were sufficient to mimic the enhanced niche activity of 3D spheroid MSCs. Thus, the molecular hierarchy in the EMT gradient among phenotypically indistinguishable MSCs revealed the previously unrecognized functional parameters in MSCs, and the EMT-enhanced "naive" mesenchymal state represents an 'activated mesenchymal niche' in 3D spheroid MSCs.
Keywords: HEMATOPOIETIC STEM-CELLS; STROMAL CELLS; TGF-BETA; TRANSITION; CANCER; METASTASIS; PROMOTES; EXPRESSION; SNAIL; PLURIPOTENCY